2007
DOI: 10.1037/0022-0167.54.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the use of demand and withdraw behavior in marriage: Examining the social structure hypothesis.

Abstract: Studies consistently show sex differences in married couples' use of demand and withdraw behavior. The social structure hypothesis proposes that these differences are the result of power differentials between spouses. This study examined the link between 3 aspects of marital power and demanding and withdrawal behavior. Contrary to social structure predictions, results showed that wives did not possess less decision-making ability or access to resources and appeared to exhibit greater situational power (i.e., d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 66 publications
6
19
1
Order By: Relevance
“…Vogel et al (2009) found that spouses who exhibited more dominant behaviors, such as interrupting, also showed more demanding behaviors than their partners in a sample of married, heterosexual couples. This finding is parallel to the finding in the current study that demanders use more hard influence tactics than withdrawers.…”
Section: Discussionmentioning
confidence: 93%
“…Vogel et al (2009) found that spouses who exhibited more dominant behaviors, such as interrupting, also showed more demanding behaviors than their partners in a sample of married, heterosexual couples. This finding is parallel to the finding in the current study that demanders use more hard influence tactics than withdrawers.…”
Section: Discussionmentioning
confidence: 93%
“…Others have shown that husbands and wives are both more likely to be in the demander role when discussing an issue they desire to change or address (Klinetob & Smith, 1996). This gender hypothesis has received much attention due to its treatment implications for helping couples who display these negative interaction patterns (Vogel, Murphy, Werner‐Wilson, Cutrona, & Seeman, 2007). Nevertheless, previous investigations of spouses' gender differences in demanding and withdrawing have relied on data collected either through questionnaires or through observed discussions in a laboratory setting.…”
Section: Demand‐withdraw Patternsmentioning
confidence: 99%
“…While mothers and fathers involved in disputed child custody cases report similar rates of controlling behaviors by their former partners, fathers report significantly higher rates of acquiescence to mothers' child rearing preferences (Newmark, Harrell, & Salem, 1995). Other research finds that many women feel entitled to dominate in the home and to engage in ''maternal gatekeeping'' (Allen & Hawkins, 1999;Straus, 1999;Vogel, Murphy, Werner-Wilson, Cutrona, & Seeman, 2007). 2 When faced with the possible ''loss'' of their children, some mothers might seek to extend or establish their control beyond the point of marital separation-and successfully so, given the currency of the patriarchal gender paradigm within the family court system ).…”
Section: The Jaffe Assessment Biasmentioning
confidence: 87%